2022 IEEE/AIAA 41st Digital Avionics Systems Conference (DASC) 2022
DOI: 10.1109/dasc55683.2022.9925817
|View full text |Cite
|
Sign up to set email alerts
|

Interference Mitigation for 5G-Connected UAV using Deep Q-Learning Framework

Abstract: To boost large-scale deployment of unmanned aerial vehicles (UAVs) in the future, a new wireless communication paradigm namely cellular-connected UAVs has recently received an upsurge of interest in both academia and industry. Fifth generation (5G) networks are expected to support this largescale deployment with high reliability and low latency. Due to the high mobility, speed, and altitude of the UAVs there are numerous challenges that hinder its integration with the 5G architecture. Interference is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, While the method mitigated interference, it primarily did in a heuristic manner, with its primary focus on energy conservation as the main objective. The authors of [17] presented an algorithm in their study that leverages DQL for intelligent interference mitigation. This approach focused on power control and aimed to solve a non-convex optimization problem to maximize the SINR using DQL techniques without the need for knowledge of CSI.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, While the method mitigated interference, it primarily did in a heuristic manner, with its primary focus on energy conservation as the main objective. The authors of [17] presented an algorithm in their study that leverages DQL for intelligent interference mitigation. This approach focused on power control and aimed to solve a non-convex optimization problem to maximize the SINR using DQL techniques without the need for knowledge of CSI.…”
Section: Related Workmentioning
confidence: 99%
“…The above literature showed that some existing approaches [1,9,10,12,14,16,18] tend to propose heuristic methods that lack a strong mathematical foundation. Some studies [1,9,10,17] have overlooked the crucial aspect of ensuring the minimum QoS for CEUEs. While certain researchers [15] have delved into complex MIMO systems and tackled the intricate problem of beamforming, there is still room for investigations in scenarios involving single-antenna systems.…”
Section: Related Workmentioning
confidence: 99%
“…To achieve a vertical seamless HO for a network as shown in figure 1, efficient techniques and algorithms must be devised. As detailed in further sections, reliable solutions exist for ground based vertical HO for UAVs [3], [4], [5]. However, air-to-space remains unexplored for UAV networks.…”
Section: Figure 1: Integrated Vertical Heterogeneous Networkmentioning
confidence: 99%
“…There are 5 elements that enable a seamless HO between the future next generation NodeB (gnB) and satellite in a future 6G network: the UAV, source future gNB, target satellite, the Access and Mobility function (AMF) and the User Plane Function (UPF). The functions of the AMF and UPF are described in [3]. preparing the different elements to carry out the process.…”
Section: F Handover Stagesmentioning
confidence: 99%
“…A power control and interference mitigation method based on DRL was created in [78]. This method was deployed in a cloud location and gets UAV measurements via the backhaul using the cloud-based architecture of 5G platforms.…”
Section: Dynamic Transmit Power Controlmentioning
confidence: 99%